Identifying priority enhancements for hazard mitigation plans in urbanizing-rural counties: an investigation of Pottawatomie County, Kansas - Thomason, Andrew Lee (Kansas State University, 2014)
Since 2005, local jurisdictions have been required to prepare hazard mitigation plans to maintain eligibility for a number of disaster-related federal grant programs. All types of communities prepare these plans, high-risk coastal communities and low-risk Great Plains communities alike. Research, both current and historic, has found hazard mitigation plans have a number of weaknesses, ranging from weak fact bases to weak mitigation actions. The purpose of this study is to explore how this research can be used to prioritize enhancements to hazard mitigation plans in growing rural counties, referred to as urbanizing rural communities, which have limited staff and resources. Specifically, Pottawatomie County, Kansas was the focus of this study. In order to prioritize enhancements, the current issues and challenges related to hazard mitigation were explored through interviews and assessing the quality of hazard mitigation plan documents. Based on the outcome of this initial analysis, plans of comparable communities were explored to identify a range of policies and methods that could be used by Pottawatomie County. Finally, these policies and methods will be prioritized based on the level of enhancement and resource requirements. This study found two possible directions for plan improvements: a combined response/mitigation planning process for a single county and strategies for participation within a regional planning context. The interviews with Pottawatomie County staff reveal an opportunity to combine phases of the emergency management cycle to boost interest and participation. The interviews also revealed a statewide shift to a regional planning process. This shift, while presenting new opportunities, will require Pottawatomie County staff to be more active and engaged to ensure the resulting regional plan will be beneficial to the county.
Keywords: Hazard Mitigation; Kansas; Planning; Rural; Land Use Planning (0536); Regional Studies (0604); Urban Planning (0999)